2017
DOI: 10.3390/w9030167
|View full text |Cite
|
Sign up to set email alerts
|

Influence Mechanisms of Rainfall and Terrain Characteristics on Total Nitrogen Losses from Regosol

Abstract: Abstract:The upper reach of the Yangtze River is an ecologically sensitive region where water loss, soil erosion, and nonpoint source (NPS) pollution are serious issues. In this drainage area, regosol is the most widely distributed soil type. Cultivation on regosol is extensive and total nitrogen (TN) has become a common NPS pollutant. Artificial rainfall experiments were conducted to reveal the influence mechanisms of rainfall and terrain on TN losses from regosol. The results showed that there were positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
3
5
0
Order By: Relevance
“…5-Ding et al [29] showed that total nitrogen load increased with increasing slope in a Yangtze River-cultivated Regosol soil.…”
Section: Appendix Amentioning
confidence: 99%
“…5-Ding et al [29] showed that total nitrogen load increased with increasing slope in a Yangtze River-cultivated Regosol soil.…”
Section: Appendix Amentioning
confidence: 99%
“…However, relationships between the subsurface hydrological process and nutrient losses were less described in literatures. For purple sloped soils, previous studies about N losses highlighted effects of rainfalls on N losses, but no relation between water flow and N losses was revealed (Ding and Zhang, 2009;Ding et al, 2017;Zhu et al, 2009). Ding et al (2017) presented negative relations between TN loads in runoff and rainfalls.…”
Section: Introductionmentioning
confidence: 90%
“…For purple sloped soils, previous studies about N losses highlighted effects of rainfalls on N losses, but no relation between water flow and N losses was revealed (Ding and Zhang, 2009;Ding et al, 2017;Zhu et al, 2009). Ding et al (2017) presented negative relations between TN loads in runoff and rainfalls. They further noted that more N losses happened due to increased runoff from increasing rainfalls.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations